Advertisement Remove all ads

Use Elementary Column Operation C2 → C2 + 2c1 in the Following Matrix Equation : (2,1,2,0)=(3,1,2,0)(1,0,-1,1 - Mathematics

Sum

Use elementary column operation C2 → C2 + 2C1 in the following matrix equation :

`[[2,1],[2,0]] = [[3,1],[2,0]] [[1,0],[-1,1]]`

Advertisement Remove all ads

Solution

The given matrix equation is in the form X =AB.

In order to apply elementary column operation on X =AB, we apply it simultaneously on X and on B of the product AB on RHS.

`[[2 , 1], [2 , 0]] = [[2 , 1], [2 , 0]]`

X = AB

We apply the transformation on the first and third matrices.

Apply C2 → C2 + 2C1

`[[2 , 1 + 4], [2, 0 + 4]] = [[3, 1],[2, 0]][[1, 0 + 2],[ -1, 1 - 2]]`

⇒ `[[2 , 5],[2, 4]] = [[3, 1],[2, 0]] [[1, 2],[-1 , -1]]`

Now you can clearly see that equation is satisfied.

  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×